2017
DOI: 10.3389/fpls.2017.01941
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Phenotyping Reveals QTL for Membrane Potential Maintenance Associated with Hypoxia and Salinity Stress Tolerance in Barley

Abstract: Waterlogging and salinity are two major abiotic stresses that hamper crop production world-wide resulting in multibillion losses. Plant abiotic stress tolerance is conferred by many interrelated mechanisms. Amongst these, the cell’s ability to maintain membrane potential (MP) is considered to be amongst the most crucial traits, a positive relationship between the ability of plants to maintain highly negative MP and its tolerance to both salinity and waterlogging stress. However, no attempts have been made to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 89 publications
(114 reference statements)
3
30
0
Order By: Relevance
“…This approach has been successfully used to reveal the linkage between the correlated traits (Fan, Shabala, Ma, Xu, & Zhou, ; Gill et al, ; Ma et al, ; Wang et al, ). For examples, a new drought tolerant QTL was confirmed to have no significant effect on agronomic trait (Fan et al, ) and a significant contribution of membrane potential to both waterlogging and salinity tolerance was identified (Gill et al, ). In the present study, SIS revealed the closest correlation with SNaC and all the three QTL for SIS were located at similar positions to those for SNaC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been successfully used to reveal the linkage between the correlated traits (Fan, Shabala, Ma, Xu, & Zhou, ; Gill et al, ; Ma et al, ; Wang et al, ). For examples, a new drought tolerant QTL was confirmed to have no significant effect on agronomic trait (Fan et al, ) and a significant contribution of membrane potential to both waterlogging and salinity tolerance was identified (Gill et al, ). In the present study, SIS revealed the closest correlation with SNaC and all the three QTL for SIS were located at similar positions to those for SNaC.…”
Section: Discussionmentioning
confidence: 99%
“…The use of covariates in QTL analysis makes it possible to detect the influences of the covariates on the traits analysed (van Ooijen, 2009). This approach has been successfully used to reveal the linkage between the correlated traits (Fan, Shabala, Ma, Xu, & Zhou, 2015;Gill et al, 2017;Ma et al, 2015;Wang et al, 2018).…”
Section: Salt Tolerance Showed the Closest Relationship With Long-dmentioning
confidence: 99%
“…Recently, a higher K + loss through the membrane under oxygen deficiency was associated with lower viability of the root cells [115]. A subsequent QTL analysis of a cross between the two cultivars revealed a major QTL on chromosome 2H underlying this tolerance trait [106]. However, it is currently not clear which gene is responsible for this trait, and whether proton pumps or K + channels are involved in the observed tolerance.…”
Section: Root Ion Transport As a Tolerance Traitmentioning
confidence: 99%
“…On the other hand, due its easy development it could provide a viable alternative for estimating the relation between various genotypes 109110 . DArT technology was successfully applied in population genetics in order to detect useful loci associated with salinity tolerance in barley 35,111,112 and bread wheat 17,113 .…”
Section: Dart Assaymentioning
confidence: 99%